Judge Hamad bin Ishaq bin Al-Bahloul, grammarian, writer, poet, speaker, narrator 1-318 AH] (Journal of the College of Basic Education, 2022)
And I am searching in the stomachs of the mothers of the books that wrote down the mention of the scholars and the greats who were involvedWith more than one science and they fought in more than one of the fields of science and literature, which they have more thanA field they were known for.. especially the books that wrote down the biographies of the nobles and the media of scholars and writers.. I got acquaintedOn a unique personality mentioned in the most important books that wrote down the history of scholars, including the worldIn which I wrote this research, and he is (Ahmed bin Ishaq bin Al-Bahloul), and I found him (grammatically and polite)A narrator, speaker, writer, and poet).Curiosity took me to get to know him more and to know such a man who spent his life in meWandering between different fields of science and literature.